Verbal conditioning awareness and intelligence - Javierto, Socorro S. (Philippine Journal of Psychology, 1971)
The effect of intelligence on verbal conditioning and awareness of the conditioning contingencies were investigated. Findings show that more intelligent subjects were conditioned sooner than lessintelligent subjects and they verbalized their awareness of the contingencies more 'often than less intelligent subjects.